Pengaruh Model Pembelajaran Mind Mapping terhadap Peningkatan Hasil Belajar Siswa pada Materi Sejarah Peradaban Islam Kelas XI di SMAN 37 Jakarta - Mutiara Fajrin Prayitno; Khairil Ikhsan Siregar (Edukhasi: Jurnal Inovasi Pendidikan, 2026)
This study aims to analyze the influence of the use of mind mapping learning models on student learning outcomes on the historical material of Islamic civilization in modern times which is motivated by student complaints who feel bored with the learning model used and feel required to memorize rather than understand the historical material of Islamic civilization. This research uses Tony Buzan's theory on the mind mapping learning model and Bloom's Taxonomy on PAI learning outcomes. The method used in this study uses quantitative methods with the type of Quasy Experimental research. The sample used was grade XI students at SMAN 37 Jakarta, each of which amounted to 15 students from the control class and experimental class. Data collection techniques used in this study consist of pre-experiment (before), treatment , observation, and post-experiment (after). Data analysis techniques used to test hypotheses are N-Gain score andpaired sample t-test. The results showed that there was a significant influence on the application of the mind mapping learning model, namely in the final stage (post-test), having a significance of 0.000 < 0.05. Then it can be seen from the average post-test score in the class given the mindmapping learning model is 91.13, greater than the control class with a conventional learning model of 84.17. These results show that there is an influence of the application of the mind mapping learning model on improving student learning outcomes in PAI subjects on the history of Islamic civilization in modern times.